Binder for lithium ion battery, aqueous binder solution for lithium ion battery, electrode slurry for lithium ion battery, electrode for lithium ion battery, and lithium ion battery

CN123023151APending Publication Date: 2026-10-30LINTEC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580024219.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-21
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0041]根据本发明,可以提供包含含有来自乙烯基醚类单体的结构单元、且合成时的残留单体的产生得到抑制的水溶性聚合物的能够形成电极的锂离子电池用粘合剂、使用了该锂离子电池用粘合剂的锂离子电池用粘合剂水溶液、锂离子电池用电极浆料、锂离子电池用电极及锂离子电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

A binder for lithium ion batteries, which contains a water-soluble polymer (A) containing structural units derived from a hydroxyl group-containing vinyl ether (a) and structural units derived from an olefinically unsaturated monomer (b) having a sulfonic acid group or a salt thereof, the content of the structural units derived from the hydroxyl group-containing vinyl ether (a) in the water-soluble polymer (A) being 5 to 80 mol% in the total structural units of the water-soluble polymer (A), and the content of the structural units derived from the olefinically unsaturated monomer (b) having a sulfonic acid group or a salt thereof in the water-soluble polymer (A) being 5 to 30 mol% in the total structural units of the water-soluble polymer (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to adhesives for lithium-ion batteries, aqueous solutions of adhesives for lithium-ion batteries, electrode slurries for lithium-ion batteries, electrodes for lithium-ion batteries, and lithium-ion batteries. Background Technology

[0002] Lithium-ion batteries are already used in electronic devices such as mobile phones and laptops. In recent years, their application in automotive and household power storage batteries has also been developing.

[0003] Lithium-ion batteries consist of components such as a positive electrode, a negative electrode, a separator, and an electrolyte. The positive and negative electrodes are manufactured by coating an electrode slurry onto a current collector and then drying it. The electrode slurry is a mixture of active materials, conductive additives, binders, solvents, etc., that enable the insertion and extraction of lithium ions.

[0004] Polyvinylidene fluoride (PVDF) and other similar materials are widely used as binders in electrode formation. However, PVDF requires dissolution in organic solvents such as N-methylpyrrolidone, and organic solvents are also used as the liquid medium in electrode slurries. In recent years, however, from the perspective of environmental impact and cost, the requirements for processes using electrode slurries employing water as the liquid medium (hereinafter referred to as "aqueous slurries") have been continuously increasing. Therefore, the development of water-soluble binders applicable to aqueous slurries has been undertaken.

[0005] Patent Document 1 discloses an adhesive used in an aqueous electrode composition for forming an electrode of a non-aqueous secondary battery, comprising a polymer having a structural unit (I) derived from an unsaturated polyalkylene glycol ether monomer (a).

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-119192 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] In the technology of Patent Document 1, unsaturated polyalkylene glycol ether monomers are copolymerized with unsaturated carboxylic acids such as acrylic acid. The water-soluble polymer, by containing structural units derived from unsaturated carboxylic acids such as acrylic acid or their salts, improves the dispersibility of active substances in the aqueous slurry.

[0011] However, according to the research of the inventors, when copolymerizing unsaturated polyalkylene glycol ether monomers and other monomers without ester bonds, especially vinyl ether monomers, with unsaturated carboxylic acids such as acrylic acid, the amount of residual monomer increases. If the amount of residual monomer is high, it leads to the problem of not being able to obtain the polymer according to the feed ratio. Furthermore, the residual monomer contributes to irreversible capacity, causing a decrease in coulombic efficiency, thus requiring a separate removal process, which in turn reduces productivity.

[0012] On the other hand, if the amount of vinyl ether monomers is reduced in order to reduce the amount of residual monomers, cracking will occur in the active material layer during electrode formation. Therefore, in the case of structural units containing vinyl ether monomers, it is difficult to obtain an adhesive that can form an electrode while suppressing the generation of residual monomers.

[0013] The present invention was made in view of the above-mentioned circumstances, and its object is to provide an electrode-forming adhesive for lithium-ion batteries comprising a water-soluble polymer containing structural units derived from vinyl ether monomers and suppressing the generation of residual monomers during synthesis, an aqueous solution of the lithium-ion battery adhesive using the lithium-ion battery adhesive, an electrode slurry for lithium-ion batteries, an electrode for lithium-ion batteries, and a lithium-ion battery.

[0014] Problem Solving Methods

[0015] The inventors conducted in-depth research and discovered that the above-mentioned problems can be solved by using water-soluble polymers containing structural units derived from specific monomers, thus completing the following invention.

[0016] That is, the present invention relates to the following [1] to [9].

[0017] [1] An adhesive for lithium-ion batteries, comprising a water-soluble polymer (A),

[0018] The water-soluble polymer (A) contains structural units derived from hydroxyl-containing vinyl ethers (a) and structural units derived from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts.

[0019] The content of the structural unit derived from the hydroxyl-containing vinyl ether (a) in the water-soluble polymer (A) is 5-80 mol% in all structural units of the water-soluble polymer (A).

[0020] The content of the structural unit from the olefinic unsaturated monomer (b) having a sulfonic acid group or its salt in the water-soluble polymer (A) is 5 to 30 moles in all the structural units of the water-soluble polymer (A).

[0021] [2] According to the adhesive for lithium-ion batteries described in [1] above, wherein,

[0022] The water-soluble polymer (A) further contains a structural unit from a compound (c) containing a (meth)acrylamide group, which is 20 to 85 moles in all the structural units of the water-soluble polymer (A).

[0023] [3] The lithium-ion battery adhesive according to [1] or [2] above, wherein,

[0024] The hydroxyl-containing vinyl ether (a) is a vinyl ether having a hydroxyalkyl group having 1 to 3 carbon atoms, or a vinyl ether having a hydroxypolyoxyalkylene chain containing 2 or more oxyalkylene units having 1 to 3 carbon atoms.

[0025] [4] The adhesive for lithium-ion batteries according to any one of [1] to [3] above, wherein,

[0026] The olefinic unsaturated monomer (b) having a sulfonic acid group or its salt is a compound having a sulfonic acid group or its salt and a (meth)acryloyl group.

[0027] [5] An aqueous solution of an adhesive for lithium-ion batteries, comprising:

[0028] The adhesive for lithium-ion batteries described in any one of [1] to [4] above, and

[0029] water.

[0030] [6] According to the above [5], the aqueous solution of the adhesive for lithium-ion batteries, wherein,

[0031] The total content of the water-soluble polymer (A) and water in the total amount of the aqueous adhesive for lithium-ion batteries is 80-100% by mass.

[0032] [7] An electrode slurry for lithium-ion batteries, comprising:

[0033] The adhesive for lithium-ion batteries described in any one of [1] to [4] above,

[0034] Active substances, and

[0035] water.

[0036] [8] An electrode for a lithium-ion battery, comprising:

[0037] The adhesive for lithium-ion batteries described in any one of [1] to [4] above, and

[0038] Active substances.

[0039] [9] A lithium-ion battery having the lithium-ion battery electrode described above [8].

[0040] The effects of the invention

[0041] According to the present invention, an electrode-forming adhesive for lithium-ion batteries comprising a water-soluble polymer containing structural units derived from vinyl ether monomers and suppressing the generation of residual monomers during synthesis, an aqueous solution of the lithium-ion battery adhesive using the lithium-ion battery adhesive, an electrode slurry for lithium-ion batteries, an electrode for lithium-ion batteries, and a lithium-ion battery can be provided. Detailed Implementation

[0042] In this specification, the lower limit and upper limit values ​​recorded in stages for the preferred numerical range can be combined independently. For example, based on the record "preferred to be 10 to 90, more preferably 30 to 60", the "preferred lower limit (10)" and the "more preferably upper limit (60)" can be combined to set "10 to 60".

[0043] In this specification, for example, "(meth)acrylic acid" means both "acrylic acid" and "methacrylic acid", and other similar terms are used in the same way.

[0044] In this specification, "structural unit" refers to a unit based on a single monomer structure formed by the polymerization of a single monomer molecule.

[0045] Adhesives for lithium-ion batteries

[0046] The lithium-ion battery adhesive of this embodiment (hereinafter also referred to as "the adhesive of this embodiment") contains a water-soluble polymer (A).

[0047] The aforementioned water-soluble polymer (A) contains structural units derived from hydroxyl-containing vinyl ethers (a) and structural units derived from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts.

[0048] The content of the structural unit derived from the hydroxyl-containing vinyl ether (a) in the above-mentioned water-soluble polymer (A) is 5 to 80 mol% in all structural units of the above-mentioned water-soluble polymer (A).

[0049] The content of the structural units derived from the olefinic unsaturated monomer (b) having a sulfonic acid group or its salt in the above-mentioned water-soluble polymer (A) is 5 to 30 moles in all structural units of the above-mentioned water-soluble polymer (A).

[0050] <Water-soluble polymer (A)>

[0051] The water-soluble polymer (A) contains structural units from a hydroxyl-containing vinyl ether (a) and structural units from an olefinic unsaturated monomer (b) having a sulfonic acid group or a salt thereof.

[0052] It should be noted that, in this specification, "vinyl ether" refers to a compound having a vinyl group and an ether oxygen atom bonded to the vinyl group.

[0053] In addition, in this specification, "olefin unsaturated monomer" refers to a monomer having an olefin unsaturated group.

[0054] In addition, “water-soluble” in the term “water-soluble polymer (A)” means that the amount of water that can be dissolved in 1 part by mass or more relative to 100 parts by mass of water at 23°C.

[0055] The water-soluble polymer (A) exhibits excellent hydrolysis resistance in alkaline environments due to the presence of structural units derived from hydroxyl-containing vinyl ethers (a).

[0056] Furthermore, the generation of residual monomers during the synthesis of water-soluble polymer (A) is suppressed due to the presence of structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts. While the reason for this is not definitively determined, one possible explanation is that the polymerization of hydroxyl-containing vinyl ethers (a) is promoted by olefinic unsaturated monomers (b) having sulfonic acid groups or their salts.

[0057] (Structural unit derived from hydroxyl-containing vinyl ether (a))

[0058] The structural unit from the hydroxyl-containing vinyl ether (a) is the structural unit formed by the addition reaction of the vinyl group present in the hydroxyl-containing vinyl ether (a).

[0059] The structural units derived from hydroxyl-containing vinyl ethers (a) contained in the water-soluble polymer (A) may be a single type or two or more types.

[0060] [Hydroxy-containing vinyl ethers (a)]

[0061] A hydroxyl-containing vinyl ether (a) is any compound having a hydroxyl group, a vinyl group, and an ether oxygen atom bonded to the vinyl group; there are no particular limitations.

[0062] The hydroxyl-containing vinyl ether (a) has one or more vinyl groups in one molecule, and from the viewpoint of suppressing gelation during synthesis, it is preferably three or less, more preferably two or less, and even more preferably one.

[0063] From the viewpoint of reactivity, flexibility, etc., the hydroxyl-containing vinyl ether (a) is preferably a vinyl ether having a hydroxyalkyl group having 1 to 3 carbon atoms, or a vinyl ether having a hydroxy polyoxyalkylene chain containing 2 or more oxyalkylene units having 1 to 3 carbon atoms.

[0064] Examples of vinyl ethers having 1 to 3 carbon atoms and containing 1 to 3 hydroxyalkyl groups include hydroxymethyl, 2-hydroxyethyl, and 3-hydroxypropyl.

[0065] Examples of vinyl ethers having a hydroxyalkyl group having 1 to 3 carbon atoms include hydroxymethyl vinyl ether, 2-hydroxyethyl vinyl ether, and 3-hydroxypropyl vinyl ether. Among these, 2-hydroxyethyl vinyl ether is preferred.

[0066] Examples of oxyalkylene units with 1 to 3 carbon atoms in a vinyl ether having a hydroxy polyoxyalkylene chain containing 2 or more oxyalkylene units of 1 to 3 carbon atoms include: oxymethylene units, oxyethylene units, oxypropylene units, etc.

[0067] The number of oxyalkylene units in the hydroxy polyoxyalkylene chain is two or more, preferably four or less, more preferably three or less, and even more preferably two.

[0068] Examples of vinyl ethers having a hydroxyl polyoxyalkylene chain comprising two or more alkylene units having one to three carbon atoms include diethylene glycol monovinyl ether, triethylene glycol monovinyl ether, dipropylene glycol monovinyl ether, and tripropylene glycol monovinyl ether. Diethylene glycol monovinyl ether is preferred.

[0069] [Content of structural units from hydroxyl-containing vinyl ethers (a)]

[0070] The content of structural units derived from hydroxyl-containing vinyl ethers (a) in the water-soluble polymer (A) is 5 to 80 mol in all structural units of the water-soluble polymer (A).

[0071] When the content of structural units from hydroxyl-containing vinyl ether (a) is 5 mol% or more, the polymer becomes soft, which can suppress electrode breakage when used as an adhesive and improve the hydrolysis resistance of the water-soluble polymer (A). In addition, when the content of structural units from hydroxyl-containing vinyl ether (a) is 80 mol% or less, the generation of residual monomers during the synthesis of the water-soluble polymer (A) can be suppressed.

[0072] From the same point of view as above, the content of structural units from hydroxyl-containing vinyl ethers (a) in the water-soluble polymer (A) is preferably 10 to 78 mol%, more preferably 20 to 75 mol%, and even more preferably 30 to 73 mol% of all structural units in the water-soluble polymer (A).

[0073] (Structural unit derived from an olefinic unsaturated monomer (b) having a sulfonic acid group or its salt)

[0074] The structural unit derived from the olefin unsaturated monomer (b) having a sulfonic acid group or its salt is a structural unit formed by the addition reaction of the olefin unsaturated group of the olefin unsaturated monomer (b) having a sulfonic acid group or its salt.

[0075] It should be noted that, in this specification, "olefin unsaturated group" refers to a functional group containing an olefin unsaturated bond.

[0076] The structural unit derived from an olefinic unsaturated monomer (b) having a sulfonic acid group or its salt can be a single type or two or more types.

[0077] [Alkenyl unsaturated monomers having a sulfonic acid group or its salt (b)]

[0078] (b) An olefinic unsaturated monomer having a sulfonic acid group or its salt thereof has a sulfonic acid group or its salt and an olefinic unsaturated group.

[0079] Examples of olefinic unsaturated groups in the olefinic unsaturated monomer (b) having a sulfonic acid group or its salt include vinyl, allyl, and (meth)acryloyl groups. Among these, (meth)acryloyl is preferred. That is, the olefinic unsaturated monomer (b) having a sulfonic acid group or its salt is preferably a compound having a sulfonic acid group or its salt, and a (meth)acryloyl group.

[0080] Salts of sulfonic acid groups refer to salts in which the sulfonic acid group (-S(=O)2OH) forms a salt structure. Examples include sodium salts of sulfonic acid groups (-S(=O)2ONa), potassium salts of sulfonic acid groups (-S(=O)2OK), and ammonium salts of sulfonic acid groups (-S(=O)2ONH4).

[0081] Examples of compounds having a sulfonic acid group or its salt and a (meth)acryloyl group include (meth)acrylamide having a sulfonic acid group or its salt, and more particularly, 2-acrylamido-2-methyl-1-propanesulfonic acid or its sodium salt.

[0082] [Content of structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts]

[0083] The content of structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts in the water-soluble polymer (A) of this embodiment is 5 to 30 moles in all structural units of the water-soluble polymer (A).

[0084] When the content of structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts is 5 mol% or more, the dispersibility of the active substance becomes good, and the generation of residual monomers during the synthesis of water-soluble polymers (A) can be suppressed. When the content of structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts is 30 mol% or less, the water absorption rate of water-soluble polymers can be suppressed.

[0085] From the same perspective as above, the content of structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts in the water-soluble polymer (A) of this embodiment is preferably 5.1 to 29 mol%, more preferably 5.3 to 20 mol%, and even more preferably 5.5 to 10 mol% in all structural units of the water-soluble polymer (A).

[0086] (Structural unit from compound (c) containing (meth)acrylamide group)

[0087] The water-soluble polymer (A) preferably further contains structural units from the compound (c) containing a (meth)acrylamide group. In this invention, compounds containing a (meth)acrylamide group having a sulfonic acid group or a salt thereof are classified as olefinically unsaturated monomers (b) having a sulfonic acid group or a salt thereof.

[0088] The structural unit of compound (c) containing a (meth)acrylamide group is formed by the addition reaction of the carbon-carbon double bond contained in the (meth)acryloyl group of compound (c).

[0089] The water-soluble polymer (A) contains structural units from compounds (c) containing (meth)acrylamide groups. The reactivity between monomers during the synthesis of water-soluble polymer (A) is enhanced, and it tends to further suppress the generation of residual monomers.

[0090] It should be noted that in this specification, "(meth)acrylamide group" refers to the group represented by the following general formula (c-1).

[0091] [Chemical Formula 1]

[0092]

[0093] (where R is in the formula) c1 It represents a hydrogen atom or a methyl group. (Indicates the bonding site.)

[0094] The structural units in the water-soluble polymer (A) derived from the compound (c) containing (meth)acrylamide groups can be a single unit or two or more units.

[0095] [Compounds containing (meth)acrylamide groups (c)]

[0096] As for compound (c) containing a (meth)acrylamide group, any compound containing the above-mentioned (meth)acrylamide group is acceptable and there is no particular limitation. For example, compounds represented by the following general formula (c-2) can be cited.

[0097] [Chemical Formula 2]

[0098]

[0099] (where R is in the formula) c1 Represents a hydrogen atom or a methyl group. R c2 and R c3 Each of the following groups independently represents a hydrogen atom, or a hydrocarbon group with 1 to 20 substituted or unsubstituted carbon atoms, R c2 With R c3 (Optional bonding to form a ring.)

[0100] In the above general formula (c-2), R is used as... c2 and R c3 Examples of substituted or unsubstituted hydrocarbon groups with 1 to 20 carbon atoms include: alkyl groups with 1 to 20 carbon atoms, alkenyl groups with 2 to 20 carbon atoms, alkynyl groups with 2 to 20 carbon atoms, and aromatic hydrocarbon groups with 6 to 20 carbon atoms, etc. As R c2 With R c3 A ring formed by bonding can be exemplified by: R c2 and R c3 The bonded nitrogen atom forms a heterocycle with 2-20 carbon atoms, which is composed of R c2 and R c3 Heterocycles formed by bonded nitrogen atoms, one or more oxygen atoms, and 2 to 20 carbon atoms.

[0101] The number of carbon atoms in a hydrocarbon group with 1 to 20 carbon atoms, whether substituted or unsubstituted, can be 1 to 10 or 1 to 5. It should be noted that this number of carbon atoms does not include the carbon atoms of the substituents.

[0102] Substituents that can be present in hydrocarbon groups with 1 to 20 carbon atoms, whether substituted or unsubstituted, include, for example, hydroxyl, halogen, cyano, nitro, carboxyl, amino, alkoxy, aryloxy, and acyloxy groups. The number of carbon atoms in the substituent can be 1 to 5 or 1 to 3.

[0103] Of the options above, from a reactivity point of view, R c2 and R c3 Hydrogen atoms are preferred.

[0104] Examples of compounds (c) containing a (meth)acrylamide group include: (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, N-tert-butyl (meth)acrylamide, N-hexyl (meth)acrylamide, and other N-alkyl (meth)acrylamides; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and other N,N-dialkyl (meth)acrylamides; N-hydroxymethyl (meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, and other (meth)acrylamides with a hydroxyalkyl group; N-acryloylpyrrolidine, 3-acryloyl-2-oxazolidinone, 4-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and other (meth)acrylamides with a cyclic structure; etc. From a reactivity point of view, (meth)acrylamide is preferred.

[0105] [Content of structural units from compound (c) containing (meth)acrylamide groups]

[0106] In the case where the water-soluble polymer (A) of this embodiment contains structural units from the compound (c) containing (meth)acrylamide groups, the content of the structural units from the compound (c) containing (meth)acrylamide groups in the water-soluble polymer (A) is preferably 10 to 90 mol%, more preferably 30 to 80 mol%, even more preferably 40 to 75 mol%, even more preferably 50 to 70 mol%, and particularly preferably 55 to 60 mol% of all structural units in the water-soluble polymer (A).

[0107] When the content of structural units from compound (c) containing (meth)acrylamide groups is at or above the lower limit mentioned above, there is a tendency to further suppress the generation of residual monomers during the synthesis of the water-soluble polymer (A). Furthermore, when the content of structural units from compound (c) containing (meth)acrylamide groups is below the upper limit mentioned above, there is a tendency to further suppress curling during electrode drying.

[0108] (Other structural units)

[0109] The water-soluble polymer (A) of this embodiment may further contain structural units (hereinafter also referred to as "other structural units") other than the hydroxyl-containing vinyl ether (a), the olefinic unsaturated monomer (b) having a sulfonic acid group or its salt, and the compound (c) containing a (meth)acrylamide group, or may not contain them.

[0110] Other monomers mentioned above include, for example: α-olefin compounds such as ethylene, propylene, n-butene, and isobutene; (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate; unsaturated carboxylic acid compounds or their salts such as acrylic acid, methacrylic acid, and sodium acrylate; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; etc.

[0111] The other structural units contained in the water-soluble polymer (A) may be a single type or two or more types.

[0112] In the case where the water-soluble polymer (A) of this embodiment contains other structural units, the content of other structural units in the water-soluble polymer (A) is preferably 60 mol% or less, more preferably 40 mol% or less, and even more preferably 20 mol% or less.

[0113] (The total amount of structural units from hydroxyl-containing vinyl ethers (a), structural units from olefinic unsaturated monomers having sulfonic acid groups or their salts (b), and structural units from compounds containing (meth)acrylamide groups (c))

[0114] The total content of structural units from hydroxyl-containing vinyl ethers (a), structural units from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts, and structural units from compounds (c) containing (meth)acrylamide groups in the water-soluble polymer (A) of this embodiment is preferably 40 to 100 mol%, more preferably 60 to 100 mol%, and even more preferably 80 to 100 mol% of all structural units in the water-soluble polymer (A).

[0115] The residual monomer content of the water-soluble polymer (A) is preferably 9.00 mol% or less, more preferably 6.00 mol% or less, even more preferably 3.00 mol% or less, and even more preferably 1.00 mol% or less.

[0116] The amount of residual monomer in the water-soluble polymer (A) can be determined by the method described in the examples.

[0117] (Method for manufacturing water-soluble polymer (A))

[0118] The water-soluble polymer (A) can be manufactured by polymerizing raw material monomers, such as a hydroxyl-containing vinyl ether (a), an olefinic unsaturated monomer (b) having a sulfonic acid group or its salt, a compound (c) containing a (meth)acrylamide group (as needed), and other monomers, in a solvent.

[0119] The polymerization method is not particularly limited, and can be any method such as solution polymerization or bulk polymerization. From a production point of view, solution polymerization is preferred, and solution polymerization using water as a solvent is more preferred.

[0120] A polymerization initiator is preferred when carrying out a polymerization reaction.

[0121] Examples of polymerization initiators include: azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropanediamine) dihydrochloride, and 2,2'-azobis(2-hydroxymethylpropanetronitrile); organic peroxides such as lauroyl peroxide, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl peroxybenzoate, and (3,5,5-trimethylhexanoyl) peroxide; and inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide. Among these, azo compounds are preferred, and 2,2'-azobis(2-methylpropanediamine) dihydrochloride is more preferred.

[0122] Polymerization initiators can be used alone or in combination of two or more.

[0123] The amount of polymerization initiator relative to the total amount of monomer (100 parts by mass) is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.5 to 3 parts by mass.

[0124] The polymerization reaction is preferably carried out while heating is applied. The reaction temperature is, for example, 50~95℃, and the reaction time is, for example, 2~8 hours.

[0125] Monomers can be added all at once or gradually.

[0126] The polymerization reaction is preferably carried out under an inert atmosphere such as nitrogen while being stirred.

[0127] <Ingredients other than water-soluble polymer (A)>

[0128] The adhesive for lithium-ion batteries in this embodiment may or may not contain components other than the water-soluble polymer (A), depending on the need.

[0129] As a component other than water-soluble polymer (A), examples of polymers other than water-soluble polymer (A) can be cited.

[0130] The content of water-soluble polymer (A) in the adhesive for lithium-ion batteries of this embodiment is preferably 90-100% by mass, more preferably 95-100% by mass, and even more preferably 99-100% by mass. The adhesive for lithium-ion batteries of this embodiment may be the water-soluble polymer (A) itself.

[0131] <Application of the adhesive for lithium-ion batteries in this embodiment>

[0132] The adhesive used in this embodiment can be used to form an electrode containing active material.

[0133] The electrode formed using the adhesive of this embodiment can be either a positive electrode or a negative electrode.

[0134] The active material used in combination with the binder of this embodiment is not particularly limited, and can be appropriately selected from known active materials. Specific examples of active materials used in combination with the binder of this embodiment are described in the section on "Electrode Slurry for Lithium-ion Batteries" described later.

[0135] [Aqueous adhesive for lithium-ion batteries]

[0136] The aqueous solution of the adhesive for lithium-ion batteries in this embodiment (hereinafter also referred to as "the aqueous solution of the adhesive in this embodiment") is an aqueous solution of the adhesive for lithium-ion batteries containing the adhesive for lithium-ion batteries in this embodiment and water.

[0137] The electrode formed using the adhesive aqueous solution of this embodiment can be either a positive electrode or a negative electrode.

[0138] From a processability point of view, the content of water-soluble polymer (A) in the adhesive aqueous solution of this embodiment is preferably 1 to 40% by mass, more preferably 5 to 30% by mass, and even more preferably 10 to 20% by mass.

[0139] The adhesive aqueous solution of this embodiment may contain other components besides the adhesive and water of this embodiment (hereinafter also referred to as "other aqueous solution components"), or it may not contain any components.

[0140] Other components of an aqueous solution include, for example, solvents other than water, thickeners, wetting agents, pH adjusters, stabilizers, surfactants, antioxidants, and preservatives. Each of these other aqueous solution components can be used individually or in combination of two or more.

[0141] From the viewpoint of further fully demonstrating the effects of the present invention, the total content of water-soluble polymer (A) and water in the total amount of adhesive aqueous solution in this embodiment is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 95 to 100% by mass.

[0142] The method for manufacturing the adhesive aqueous solution in this embodiment is not particularly limited. For example, if water is used as a solvent when synthesizing the water-soluble polymer (A) and the water-soluble polymer (A) is obtained in the form of an aqueous solution, the aqueous solution of the water-soluble polymer (A) can be used directly as the adhesive aqueous solution in this embodiment.

[0143] Alternatively, if necessary, the water-soluble polymer (A) synthesized in the solvent can be dissolved in water at a desired time after separation. Other aqueous solution components can be added at any time.

[0144] Electrode slurry for lithium-ion batteries

[0145] The electrode slurry for lithium-ion batteries in this embodiment (hereinafter also referred to as "the electrode slurry of this embodiment") is an electrode slurry for lithium-ion batteries containing the binder for lithium-ion batteries of this embodiment, active material and water.

[0146] The electrode paste of this embodiment can be dried after being coated onto the current collector, thereby forming an active material layer on the current collector containing the active material and the binder of this embodiment.

[0147] The electrode formed using the electrode slurry of this embodiment can be either a positive electrode or a negative electrode.

[0148] The active material contained in the electrode paste of this embodiment is not particularly limited, and can be appropriately selected from known active materials for positive electrodes and active materials for negative electrodes, depending on the purpose.

[0149] Examples of active materials used as cathodes include: lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, ternary cathode materials, and quaternary cathode materials. For example, LiNi... 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi x Co y Mn zO2 (0<x<1, 0<y<1, 0<z<1 and x+y+z=1), the nickel-cobalt-manganese ternary positive electrode material (NCM), LiNi 0.8 Co 0.15 Al 0.05 O2 and the like, the nickel-cobalt-aluminum ternary positive electrode material (NCA) represented by LiNi x Co y Al z O2 (0<x<1, 0<y<1, 0<z<1 and x+y+z=1), and the like. The active material for the positive electrode may be used alone, or two or more thereof may be used in combination.

[0150] The average particle diameter (D 50 ) of the active material for the positive electrode is not particularly limited, and may be, for example, 0.01 to 30 μm, 0.1 to 20 μm, or 1 to 15 μm.

[0151] Examples of the active material for the negative electrode include graphite, hard carbon, lithium titanate, Si, SiO, lithium-doped SiO, and the like. The active material for the negative electrode may be used alone, or two or more thereof may be used in combination.

[0152] The average particle diameter (D 50 ) of the active material for the negative electrode is not particularly limited, and may be, for example, 0.1 to 50 μm, 0.5 to 45 μm, or 1 to 30 μm.

[0153] The shape of the active material is not particularly limited, and may be, for example, crushed, spherical, flat, fibrous, or the like.

[0154] Here, since the water-soluble polymer (A) contained in the binder of the present embodiment has a structural unit derived from a hydroxyl group-containing vinyl ether (a), it has excellent hydrolysis resistance in an alkaline environment. Therefore, by using the binder of the present embodiment in combination with an active material that exhibits alkalinity in the state of an aqueous slurry, electrode production can be carried out more stably than with an aqueous slurry using a conventional water-soluble binder.

[0155] From this point of view, the active material contained in the electrode slurry of the present embodiment is preferably an active material that exhibits a high pH in the state of an aqueous slurry. Examples of the active material that exhibits a high pH in the state of an aqueous slurry include lithium-doped SiO, ternary positive electrode materials, and the like.

[0156] In the electrode slurry of the present embodiment, the content of the binder of the present embodiment is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and still more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the active material.

[0157] When the content of the adhesive in this embodiment is at or above the aforementioned lower limit, it tends to enable the active material to bond more firmly. Furthermore, when the content of the adhesive in this embodiment is below or above the aforementioned upper limit, it tends to suppress the increase in electrode resistance.

[0158] The electrode paste of this embodiment may contain conductive additives as needed.

[0159] Examples of conductive additives include: various types of graphite; carbon blacks such as acetylene black, Ketjen black, furnace black, and channel black; carbon fibers such as carbon nanofibers and carbon nanotubes; and metallic materials such as nickel, aluminum, and stainless steel.

[0160] The shape of the conductive additive is not particularly limited; it can be in the form of particles or fibers.

[0161] Conductive additives can be used alone or in combination of two or more.

[0162] When the electrode paste of this embodiment contains a conductive additive, the content of the conductive additive is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the active material, more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass.

[0163] From the viewpoint of coating properties, the concentration of solid components in the electrode slurry of this embodiment is preferably 20-90% by mass, more preferably 25-85% by mass, and even more preferably 30-80% by mass. It should be noted that, in this specification, the solid components of the electrode slurry refer to components other than the liquid medium.

[0164] The electrode paste of this embodiment may contain the binder, active material, and water of this embodiment, as well as components other than conductive additives used as needed (hereinafter also referred to as "other paste components"), or it may not contain any of these components. Examples of other paste components include those identical to the other aqueous solution components described above.

[0165] The method for manufacturing the electrode paste in this embodiment is not particularly limited. For example, it can be manufactured by mixing the adhesive of this embodiment or the aqueous solution of the adhesive of this embodiment, the active substance, the conductive additive used as needed, the solvent such as water, and other paste components by a known method.

[0166] Since the binder of this embodiment suppresses the generation of residual monomers, an aqueous solution of the water-soluble polymer (A), which contains water as a reaction solvent when synthesizing the water-soluble polymer (A), can be directly used in the manufacture of electrode paste.

[0167] As a mixing device, a mixing machine such as a ball mill, sand mill, planetary mixer, paint shaker, homogenizer, dispersion homogenizer, or homogenizer can be used.

[0168] Electrodes for lithium-ion batteries

[0169] The lithium-ion battery electrode of this embodiment (hereinafter also referred to as "the electrode of this embodiment") is a lithium-ion battery electrode containing the lithium-ion battery binder and active material of this embodiment.

[0170] The electrode in this embodiment can be either a positive electrode or a negative electrode.

[0171] The electrode of this embodiment preferably has an active material layer on the current collector containing an active material and the binder of this embodiment.

[0172] For the electrode in this embodiment, the thickness of the active material layer is not particularly limited, for example, it is 100~300μm.

[0173] The description of the active substances contained in the electrode of this embodiment is the same as the description of the active substances contained in the electrode slurry of this embodiment described above.

[0174] In the electrode of this embodiment, the content of the binder relative to 100 parts by mass of the active material is the same as the preferred range described in the description of the electrode slurry of this embodiment.

[0175] Furthermore, the electrode of this embodiment may contain the aforementioned conductive additive. In the electrode of this embodiment, the content of the conductive additive relative to 100 parts by mass of the active material is the same as the preferred range described in the description of the electrode slurry of this embodiment.

[0176] In addition, the electrode of this embodiment may contain the other slurry components and other aqueous solution components listed above.

[0177] The current collector is preferably formed of sheet-like metal.

[0178] Metals used as current collectors include, for example, iron, copper, aluminum, nickel, and stainless steel. Among these, aluminum foil is preferred as the current collector for the positive electrode, and copper foil is preferred as the current collector for the negative electrode.

[0179] The thickness of the current collector is, for example, 5~20μm.

[0180] The electrode of this embodiment can be manufactured by coating the electrode slurry of this embodiment onto the current collector and then drying it.

[0181] Examples of methods for coating the electrode paste of this embodiment onto the current collector include: reverse roller coating, scraper coating, direct roller coating, doctor blade coating, extrusion coating, curtain coating, gravure coating, rod coating, dip coating, and extrusion coating.

[0182] The electrode paste of this embodiment can be applied to only one side of the current collector or to both sides. When the electrode paste is applied to both sides of the current collector, it can be applied to each side separately or to both sides simultaneously. Furthermore, the electrode paste can be applied continuously to the entire surface of the current collector or applied intermittently. The amount and range of the electrode paste applied can be appropriately determined based on factors such as the size of the battery.

[0183] Methods for drying electrode paste coated on current collectors include, for example, methods such as blowing hot air, vacuum drying, and methods using electromagnetic waves such as infrared, far-infrared, and near-infrared heaters.

[0184] The drying temperature of the electrode slurry is, for example, 80~150℃, and the drying time is, for example, 1~30 minutes.

[0185] The resulting electrodes can be shaped by cutting or other processes as needed.

[0186] [Lithium-ion battery]

[0187] The lithium-ion battery of this embodiment is a lithium-ion battery having the electrodes for a lithium-ion battery of this embodiment.

[0188] Examples of lithium-ion batteries in this embodiment include lithium-ion secondary batteries comprising a positive electrode, a negative electrode, an electrolyte, and a separator.

[0189] In the lithium-ion battery of this embodiment, at least one of the positive electrode and the negative electrode includes the electrode of this embodiment. Under this premise, it may include electrodes other than the electrode of this embodiment.

[0190] Electrodes, electrolytes, and separators other than those in this embodiment can be appropriately selected from known materials depending on the application.

[0191] The shape of the lithium-ion battery in this embodiment is not particularly limited, and it can be any shape such as coin-shaped, button-shaped, sheet-shaped, cylindrical, square, or flat.

[0192] Example

[0193] The present invention will now be described in further detail based on embodiments, but the present invention is not limited to these examples.

[0194] [Preparation of an aqueous solution of binder for lithium-ion batteries]

[0195] Example 1

[0196] 1274.8 g of purified water, 200.0 g of diethylene glycol monovinyl ether, 163.0 g of an aqueous solution of sodium 2-acrylamido-2-methyl-1-propanesulfonate (50% by mass), and 160.0 g of an aqueous solution of acrylamide (50% by mass) were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas to remove oxygen from the reaction system. A solution of 2.4 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 24.0 g of purified water was then added, and the reaction was carried out at 80°C for 4 hours. Then, 1106.6 g of purified water was added to obtain an aqueous solution of water-soluble polymer (A). This aqueous solution of water-soluble polymer (A) was used as an aqueous binder for lithium-ion batteries (the content of water-soluble polymer (A) was 13% by mass).

[0197] Example 2

[0198] 743.2 g of purified water, 200.0 g of 2-hydroxyethyl vinyl ether, and 200.0 g of an aqueous solution of sodium 2-acrylamido-2-methyl-1-propanesulfonate (50% by mass) were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The mixture was heated to 55°C, and nitrogen was introduced to remove oxygen from the reaction system. A solution of 2.4 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 24.0 g of purified water was then added, and the mixture was heated to 80°C and reacted for 4 hours. Then, 1712.5 g of purified water was added to obtain an aqueous solution of water-soluble polymer (A). The obtained aqueous solution of water-soluble polymer (A) was used as an aqueous binder for lithium-ion batteries (the content of water-soluble polymer (A) was 13% by mass).

[0199] Comparative Example 1

[0200] In Example 1, 163.0 g of sodium acrylate aqueous solution (concentration 32% by mass) was used instead of 163.0 g of sodium 2-acrylamido-2-methyl-1-propanesulfonate aqueous solution (concentration 50% by mass). Otherwise, an aqueous solution of the water-soluble polymer was prepared in the same manner as in Example 1. The resulting aqueous solution of the water-soluble polymer was used as an aqueous solution of the binder for lithium-ion batteries (the content of the water-soluble polymer was 13% by mass).

[0201] Comparative Example 2

[0202] 1805.53 g of purified water, 25.00 g of diethylene glycol monovinyl ether, 644.64 g of 50% (w / w) acrylamide aqueous solution, and 0.38 g of sodium methacrylate sulfonate were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The mixture was heated to 55°C, and nitrogen gas was introduced to remove oxygen from the reaction system. A solution of 3.48 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 41.72 g of purified water was then added, and the mixture was heated to 80°C and reacted for 4 hours. Then, 180.63 g of purified water was added to obtain an aqueous solution of the water-soluble polymer. This aqueous solution of the water-soluble polymer was used as an aqueous binder for lithium-ion batteries (the content of the water-soluble polymer was 13% (w / w)).

[0203] Comparative Example 3

[0204] 792.80 g of purified water and 200.00 g of diethylene glycol monovinyl ether were added to a reaction apparatus equipped with a stirrer, thermometer, reflux condenser, and nitrogen inlet. The temperature was raised to 55°C, and nitrogen gas was introduced to remove oxygen from the reaction system. A solution containing 2.00 g of 2,2'-azobis(2-methylpropanediamine) dihydrochloride and 20.00 g of purified water was then added, and the mixture was heated to 80°C and reacted for 4 hours. Finally, 545.05 g of purified water was added, and the reaction solution was further purified. 1 The H-NMR analysis only confirmed the peak of the monomer, therefore it was determined that polymerization had not occurred.

[0205] [Manufacturing of electrode slurry and electrodes for lithium-ion batteries]

[0206] Add 13.6 g of the aqueous solution of the lithium-ion battery binder obtained in the various examples and comparative examples, and carbon black (manufactured by MTI Corporation, trade name "Super C65", specific surface area based on BET method: 62 m²) as a conductive additive to a glass container (capacity: 140 mL). 2 0.84g of purified water and 41.4g of purified water were mixed at 2000 rpm for 30 minutes using a disperser (Primix, trade name "LABOLUTION", stirring part: Homo Disper 2.5). Graphite (manufactured by Jiangxi Zichen Technology Co., Ltd., artificial graphite G1-C, average particle size D) was then added as an active ingredient. 50 35.0g of lithium-ion battery electrode slurry (20μm) was stirred at 2000rpm for 10 minutes using the above-mentioned disperser, and then degassed for 5 minutes under 0.04 atmosphere pressure, thereby obtaining a solid component concentration of 50% by mass.

[0207] The prepared lithium-ion battery electrode slurry was coated onto copper foil (manufactured by UACJ Corporation, rolled copper foil, 10 μm thick) using a coater with a 280 μm gap. Then, it was dried in an oven at 120°C for 10 minutes to obtain a lithium-ion battery electrode (negative electrode) with an active material layer of 150 μm thickness on the current collector (copper foil).

[0208] [Evaluation of Electrode Formation Performance]

[0209] By visually inspecting the surface of the active material layer of the lithium-ion battery electrode manufactured by the above method, cases where the active material layer did not crack were designated as "A", and cases where cracks appeared were designated as "F". It should be noted that, as mentioned above, Comparative Example 3 was designated as "unevaluable" because no water-soluble polymer was obtained.

[0210] [Methods for determining residual monomer content]

[0211] Using the aqueous adhesive for lithium-ion batteries obtained in the examples and comparative examples as samples, the following tests were conducted. 1 1H nuclear magnetic resonance (NMR) spectroscopy analysis was used to quantify the amount of residual monomer in the aqueous solution. In Table 1, the amount of residual monomer is expressed as the ratio (molar %) of the residual monomer to the total amount of monomer used as a raw material for the water-soluble polymer. The NMR apparatus used was of the specifications described below.

[0212] Device: Bruker, product name "Biospin Avance 500"

[0213] Deuterated solvent: Heavy water (D2O)

[0214]

[0215] The detailed information of the monomers in Table 1 is as follows.

[0216] DEGV: Diethylene glycol monovinyl ether

[0217] HEVE: 2-Hydroxyethyl vinyl ether

[0218] ATBSNa: Sodium salt of 2-acrylamide-2-methyl-1-propanesulfonate

[0219] SMAS: Sodium methylpropenesulfonate

[0220] AM: Acrylamide

[0221] SA: Sodium acrylate

[0222] As shown in Table 1, the aqueous adhesive solution for lithium-ion batteries obtained in Examples 1 and 2 of this embodiment can form electrodes and suppress the generation of residual monomers during the synthesis of water-soluble polymers.

Claims

1. An adhesive for lithium-ion batteries, comprising a water-soluble polymer (A), The water-soluble polymer (A) contains structural units derived from hydroxyl-containing vinyl ethers (a) and structural units derived from olefinic unsaturated monomers (b) having sulfonic acid groups or their salts. The content of the structural unit derived from the hydroxyl-containing vinyl ether (a) in the water-soluble polymer (A) is 5-80 mol% in all structural units of the water-soluble polymer (A). The content of the structural unit from the olefinic unsaturated monomer (b) having a sulfonic acid group or its salt in the water-soluble polymer (A) is 5 to 30 moles in all the structural units of the water-soluble polymer (A).

2. The adhesive for lithium-ion batteries according to claim 1, wherein, The water-soluble polymer (A) further contains a structural unit from a compound (c) containing a (meth)acrylamide group, which is 10 to 90 moles in all the structural units of the water-soluble polymer (A).

3. The adhesive for lithium-ion batteries according to claim 1 or 2, wherein, The hydroxyl-containing vinyl ether (a) is a vinyl ether having a hydroxyalkyl group having 1 to 3 carbon atoms, or a vinyl ether having a hydroxypolyoxyalkylene chain containing 2 or more oxyalkylene units having 1 to 3 carbon atoms.

4. The adhesive for lithium-ion batteries according to claim 1 or 2, wherein, The olefinic unsaturated monomer (b) having a sulfonic acid group or its salt is a compound having a sulfonic acid group or its salt and a (meth)acryloyl group.

5. An aqueous solution of an adhesive for lithium-ion batteries, comprising: The adhesive for lithium-ion batteries as described in claim 1 or 2, and water.

6. The aqueous adhesive solution for lithium-ion batteries according to claim 5, wherein, The total content of the water-soluble polymer (A) and water in the total amount of the aqueous adhesive for lithium-ion batteries is 80-100% by mass.

7. An electrode slurry for lithium-ion batteries, comprising: The adhesive for lithium-ion batteries as described in claim 1 or 2 Active substances, and water.

8. An electrode for a lithium-ion battery, comprising: The adhesive for lithium-ion batteries as described in claim 1 or 2, and Active substances.

9. A lithium-ion battery having the electrode for a lithium-ion battery as described in claim 8.

Citation Information

Patent Citations

  • Binder for aqueous system electrode composition for nonaqueous secondary battery

    JP2011119192A